Sensitization of cancer cells to DNA-damaging agents by expression of the REV1 C-terminal domain: Implications for chemotherapy - Ke Bian; Charley C. Gruber; Emine Byers; Paul Leclerc; Michael T. Hemann; Graham C. Walker (Proceedings of the National Academy of Sciences, 2025)
The mutagenic translesion synthesis (TLS) pathway, which is critically dependent on REV1’s ability to recruit inserter TLS polymerases and the POLζ extender polymerase, enables cancer cells to bypass DNA lesions while introducing mutations that likely contribute to the development of chemotherapy resistance and secondary malignancies. Targeting this pathway represents a promising therapeutic strategy. Here, we demonstrate that the expression of the C-terminal domain (CTD) of human REV1, a ca. 100 amino acid scaffold essential for TLS polymerase interactions, disrupts REV1/POLζ-dependent TLS in mammalian cells. Inducible expression of REV1-CTD in multiple human and murine cancer cell lines sensitizes cells to DNA-damaging agents such as cisplatin, benzo[a]pyrene diol epoxide, and methyl methanesulfonate, without intrinsic cytotoxicity. REV1-CTD expression increases genomic instability, decreases mutagenesis, and enhances G2 arrest following genotoxic stress. Mutational disruption of the CTD’s interaction interfaces abrogates these effects, confirming a dominant-negative mechanism via sequestration of TLS components. In a xenograft mouse model, REV1-CTD expression markedly enhances cisplatin efficacy, significantly reducing tumor burden. These findings establish the REV1-CTD as an effective dominant-negative inhibitor of TLS and support its development as a therapeutic agent delivered to cancer cells to enhance the efficacy of genotoxic chemotherapy.